Real-life outcomes of COVID-19 vaccination in kidney transplant patients: a single-center experience - Ay, Nurettin; Danış, Ramazan (The Journal of Infection in Developing Countries, 2023)
Introduction: In this study, it was aimed to investigate the clinical (real-life) impact of the vaccination protocol on patients undergoing kidney transplantation during the COVID-19 pandemic. Methodology: A total of 260 patients who underwent kidney transplantation between June 2012 and May 2022 were retrospectively evaluated. Patients chose vaccination Sinovac-CoronaVac (CoronaVac) and/or BNT162b2 (Biontech), the first vaccine available in the country) in line with the regulations and recommendations of the Ministry of Health. The relationship between vaccination, hospitalization, and mortality in cases diagnosed with COVID-19 was investigated. The prevalence of COVID-19 in patients, the rate of hospital admission, and the mortality of patients before and after the national vaccination program were examined. Results: The study included a total of 260 kidney transplant patients (Female, n = 107 (41%); male, n = 153 (59%). The mean age of patients was 38.42 (11-75). A total of 108 (41.5%) patients were diagnosed with COVID-19. Seven (6.5%) patients died and 221 (85%) patients were vaccinated after the national vaccination program. During the follow-up period, 108 (41.5%) patients were diagnosed with COVID-19. There was no significant difference in terms of hospitalization between two groups. However, there was a significant difference in terms of admission to intensive care unit and mortality (p < 0.001). Conclusions The majority of cases that died were unvaccinated. However, repeated vaccinations may not adequately protect all transplant recipients. There is a need to develop personalized treatment and prevention strategies in transplantation cases.